2013
DOI: 10.18553/jmcp.2013.19.7.558
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Combined Pharmacist and Social Worker Program to Reduce Hospital Readmissions

Abstract: BACKGROUND: The Patient Protection and Affordable Care Act (2010) directed the Centers for Medicare and Medicaid Services to implement a hospital readmissions reduction program that reduces payments to hospitals for excess readmissions that began in October 2012. As such, hospitals across the country have been trying to identify and implement successful strategies for reducing hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…17,19,49,54,98,102 Consistent with our results, few studies examining the impact of care transitions programs on medication-related outcomes did not find any significant effect on medication-related outcomes. For instance, Kripalani and colleagues did not find any positive effect of pharmacist-led interventions on post discharge medication errors in patients with acute coronary syndromes or acute decompensated heart failure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…17,19,49,54,98,102 Consistent with our results, few studies examining the impact of care transitions programs on medication-related outcomes did not find any significant effect on medication-related outcomes. For instance, Kripalani and colleagues did not find any positive effect of pharmacist-led interventions on post discharge medication errors in patients with acute coronary syndromes or acute decompensated heart failure.…”
Section: Discussionsupporting
confidence: 88%
“…To date, studies evaluating the impact of pharmacist-led interventions on medication errors, medication adherence, and health care utilization after hospital discharge have shown mixed results. 17,19,49,54,98,99 For example, Kripalani and colleagues found that among patients hospitalized with acute coronary syndromes or acute decompensated heart failure, the pharmacist-led interventions did not significantly reduce medication errors after hospital discharge. 19 Schnipper and colleagues found that pharmacist-provided interventions for patients discharged home from the general medicine service was associated with a lower rate of preventable adverse drug events (ADE).…”
Section: Chapter 4 Effect Of a Care Transitions Program On Medicatiomentioning
confidence: 99%
“…TOC interventions performed by pharmacists in the hospital reduce readmissions and medication errors. Services can be provided in the emergency department (ED), upon admission, during transfer between units/services, at discharge, or after discharge through a follow‐up telephone call . Table provides additional details for select examples of pharmacist TOC interventions in the hospital setting.…”
Section: Best Practicesmentioning
confidence: 99%
“…After 30 days, hospital readmission rates were 10% for the program patients and 30% for the routine care patients. 8 Health professionals agree clear communication is the most basic, but challenging, part of patient care during transitions.…”
Section: Psychosocial Assessment and Social Workersmentioning
confidence: 99%